Fucoxanthin alleviates methamphetamine-induced neurotoxicity possibly via the inhibition of interaction between Keap1 and Nrf2. (November 2021) - Wei, Jiaxin; Mou, Chenye; Bao, Yongjie; Xie, Yanfei; Jin, Haixiao; Shen, Haowei; Zhou, Wenhua; Zhang, Jinrong; He, Shan; Chen, Bojun; Liu, Lin; Wu, Xiang; et al.
Graphical abstract: Highlights: Fucoxanthin inhibits methamphetamine-induced neuronal apoptosis and oxidative stress. Fucoxanthin promotes Nrf2 translocation via the activation of the Akt pathway. Fucoxanthin prevents Nrf2 degradation possibly via inhibiting Keap1-Nrf2 interaction. Fucoxanthin as a functional natural food for treating methamphetamine abuse. Abstract: Fucoxanthin, a carotenoid from edible algae such as Sargassum horneri, has been widely used as a functional food for treating obesity, and was reported to produce neuroprotective effects against various neurotoxins. Here we evaluated the anti-methamphetamine neuroprotective effects of fucoxanthin in PC12 cells. Pretreatment with fucoxanthin prevented methamphetamine-induced increase of reactive oxygen species (ROS) and neuronal apoptosis. Furthermore, fucoxanthin increased the nuclear translocation of nuclear factor-erythroid 2-related factor 2 (Nrf2) and the expression of heme oxygenase-1 (HO-1), an antioxidant enzyme positively regulated by Nrf2. In addition, fucoxanthin could reverse the decreased expression of phospho-Ser473-Akt, an upstream molecule which prevents Nrf2 degradation and increases Nrf2 nuclear translocation. Most importantly, fucoxanthin showed a high affinity with Kelch-like ECH-associated protein-1 (Keap1), via the action on Keap1-Nrf2 binding pocket, suggesting that fucoxanthin might also facilitate the dissociation of Keap1-Nrf2 complex, and enhance Nrf2 nuclear translocation. All these results implied that fucoxanthin might be developed as an antidote of methamphetamine.